Integrating Ndolalak Dance in Islamic Multicultural Education: Cultural Preservation and Character Building - Oktaviana, Mutiara Rahma; Ramadan , Fadilah Dea; Mubin, Nurul (AJIRSS: Asian Journal of Innovative Research in Social Science, 2024)
This article examines the importance of incorporating the Ndolalak Dance in Islamic-based multicultural education as a step to preserve local culture and build student character. The Ndolalak dance, which originates from Purworejo, is a traditional art form that not only displays the beauty of movement but also contains moral and spiritual values that align with Islamic teachings. In the context of multicultural education, this dance functions as a means of introducing cultural diversity and supporting understanding of the principles of tolerance and mutual respect between cultures. Through interactive and fun learning, students not only learn dance techniques, but also understand the meaning and symbolism contained in the Ndolalak Dance.This article also highlights various teaching methods that can be used to integrate this dance into the curriculum, such as organizing workshops, performances, and discussions regarding cultural and religious values. Furthermore, this article explains how the incorporation of Ndolalak Dance in education can contribute to the development of student character, including discipline, cooperation, and love of local culture. By involving the community and educational stakeholders, it is hoped that cultural preservation through Islamic-based multicultural education can be implemented effectively and have a positive impact onthe younger generation in understanding and appreciating diversity. Overall, this article emphasizes that the incorporation of Ndolalak Dance in Islamic multicultural education not only functions to preserve culture but also as a strategy to form strong character, thereby creating a harmonious and mutually respectful society amidst diversity